Effects of some indigenous plant seed extracts on the Haematology of a predatory fish Singhi Heteropneustes fossilis (Bloch) - Nasiruddin, Munira; Azadi, Mohammad Ali; Rahman, Monika; Rahman, Israt Ara Shazia (Chittagong University Journal of Biological Sciences, 2013)
Haemolytic effects of different extracts of five indigenous plant seeds viz. Datura innoxia (Mill) (Shada Dhutra), Clerodendrum viscosum (Vent.) (Vat), Amoora rohituka (Roxb.) Wt. ct. Arnott (Pitraj), Acacia auriculiformis A. Cunn. Ex. Benth. (Akashmoni) and Pongamia pinnata (L.) Pierre (Karinja) were studied upon a predatory fish, Singhi, Heteropneustes fossilis (Bloch) under laboratory conditions. Toxicants inducing effects on the blood parameters included decreased RBC and WBC counts, low haemoglobin percentage and decreased PCV (packed cell volume), MCV (mean corpuscular volume) and MCH (mean corpuscular haemoglobin). Haemolysis action included shrunken or swollen RBCs, granulated nuclei of RBCs and pyknotic nuclei of WBCs, clumping of RBCs and syncitium of RBC matrix. Damage of blood cells with absolute ethyl alcohol extract was most pronounced with all of the seed extracts. The order of toxicity of the five seed extracts on the blood parameters of Singhi was: D. innoxia < A. auriculaerformis < P. pinnata < C. viscosum < A. rohituka seed extracts. On the basis of haemolysis the toxicity was: A. rohituka > C. viscosum > P. pinnata > D. innoxia > A. auriculiformis seed extracts. DOI: http://dx.doi.org/10.3329/cujbs.v6i1-2.17078 The Chittagong Univ. J. B. Sci.,Vol. 6(1&2):11-25, 2011